Effect of Dioptric Blur on Pattern-Reversal and Motion-Onset VEPs as Used in Clinical Research - Kordek, David; Voda, Petr; Young, Laura K; Kremlacek, Jan (Translational vision science & technology, 2022)
PURPOSE: To describe the effect of dioptric blur on visual evoked potentials (VEPs) induced by motion onset (MO-VEPs). METHODS: The effect of dioptric blur up to 4 D on MO-VEPs was tested on 12 subjects using central, peripheral, and full-field stimulation with a low-contrast structure of concentric circles with spatial frequency <1 c/°. The results were compared to VEPs evoked by 15' and 60' checkerboard pattern-reversal (PR-VEPs). The relationship between peak time and interpeak amplitude of the dominant components was related to the level of dioptric blur using linear regression. RESULTS: The MO-VEPs did not show a significant peak prolongation (P > 0.28) or amplitude attenuation (P > 0.14) with the blur, whereas for the PR-VEPs we observed a significant decrease in amplitude (P < 0.001) and increase in peak time (P < 0.001) for both checkerboard sizes. CONCLUSIONS: For MO-VEPs induced by radial motion of low contrast and low spatial frequency pattern, the change in retinal blur does not affect the peak time or the interpeak amplitude of the dominant N2 component. TRANSLATIONAL RELEVANCE: The resistance to retinal blur that we demonstrated for MO-VEP provides a diagnostic opportunity to test the integrity of the visual system and reveal a retrobulbar impairment even in uncorrected refractive errors.
Keywords: Evoked Potentials, Visual; lidé; zrakové evokované potenciály; Humans